Kristendommens aktualitet som viljen til sandhed - Karlsen, Mads Peter (Dansk Teologisk Tidsskrift, 2011)
This article discusses the question of the influence and potential of Christianity in contemporary secularized culture. I take as my starting point the twofold thesis that ‘God is dead’ and ‘Christianity survived the death of God’. In section 1 and 2 I demonstrate how Friedrich Nietzsche and Michel Foucault have elaborated this thesis in a somewhat similar manner by criticising the ideological workings of what in the words of Nietzsche could be called the Christian ‘will to truth’. In section 3 I argue that Slavoj Žižek’s recent engagement with theology allow for another reading of the Christian truth-seeking, which in contrast brings out a potential for a critique of ideology. The difference between these two readings can be summarized as two interpretations of the famous words in The Gospel of John, “you will know the truth, and the truth will set you free.” Thus, Christianity does not only entail the suppressive danger of an obligation to tell the truth about oneself at any prize, it also offers the liberating prospective in being true to the manifestation of the death of God on the cross.